Body Mass Index and Weight Loss in Metastatic Colorectal Cancer in CALGB (Alliance)/SWOG 80405. Issue 3 (31st March 2020) - Guercio, Brendan J; Zhang, Sui; Venook, Alan P; Ou, Fang-Shu; Niedzwiecki, Donna; Lenz, Heinz-Josef; Innocenti, Federico; Mullen, Brian C; O'Neil, Bert H; Shaw, James E; Polite, Blase N; Hochster, Howard S; et al.
Abstract: Background: In nonmetastatic colorectal cancer, overweight and mild-to-moderately obese patients experience improved outcomes compared with other patients. Obesity's influence on advanced or metastatic colorectal cancer (mCRC) is relatively unexplored. Methods: We conducted a prospective body mass index (BMI) companion study in Cancer and Leukemia Group B (now Alliance)/SWOG 80405, a phase III metastatic colorectal cancer (mCRC) treatment trial. BMI was measured at trial registration. Primary and secondary endpoints were overall and progression-free survival, respectively. To minimize confounding by poor and rapidly declining health, we used Cox proportional hazards regression to adjust for known prognostic factors, comorbidities, physical activity, and weight loss during the 6 months prior to study entry. We also examined weight loss prior to enrollment as an independent predictor of patient outcome. All statistical tests were two-sided. Results: Among 2323 patients with mCRC, there were no statistically significant associations between BMI and overall or progression-free survival (adjusted P trend = .12 and .40, respectively). Weight loss during the 6 months prior to study entry was associated with shorter overall and progression-free survival; compared with individuals with stable weight ±4.9%, individuals with weight loss greater than 15% experienced an adjusted hazard ratio of 1.52 for all-cause mortality (95% confidence interval [CI] = 1.26 to 1.84; P trend < .001) and of 1.23 for disease progression or death (95% CI = 1.02 to 1.47; P trend = .006). Conclusions: In this prospective study of patients with mCRC, BMI at time of first-line chemotherapy initiation was not associated with patient outcome. Weight loss prior to study entry was associated with increased risk of patient mortality and disease progression.